Assessing the impact of mobile technology on order verification during pharmacist participation in patient rounds. - Ray, Shaunta' M.; Clark, Shirmil; Jeter, Julie W.; Treadway, Sarah A. (American Journal of Health-System Pharmacy, 2013)
Purpose. Pharmacists' use of mobile technology (MT) to verify medication orders placed during their participation in medical rounds is investigated. Methods. A retrospective observational study was conducted at a large academic medical center to assess the impact of MT on the average time to pharmacist verification of medication orders written by general medicine staff during pharmacist participation in patient rounds. A total of 260 medication orders for 129 patients were evaluated: 146 orders processed over a one-month period during which rounding pharmacists verified orders using stationary computer terminals on patient care units and 114 orders processed using an MT device. The primary endpoint was the average time to pharmacist verification for all medication orders; average verification times for orders for specific medication classes (analgesics, antibiotics, antidiabetes drugs, and antihypertensives) were also evaluated. Results. Overall, the average time to order verification was significantly lower with the use of the MT device compared with non-MT-assisted order verification (7.5 minutes versus 38.9 minutes, p < 0.001), with significant (p < 0.001) time benefits favoring MT-assisted verification for all order subsets within the evaluated medication classes. Challenges posed by the use of MT-assisted order verification included the selected device's relatively small keyboard and the frequent loss of network connections as the pharmacist moved from floor to floor within the hospital. Conclusion. Clinical pharmacists' use of an MT device to verify medication orders written during patient care rounds can significantly decrease the average time required for order verification relative to the use of stationary computer terminals.